2023
DOI: 10.1021/acssynbio.3c00287
|View full text |Cite
|
Sign up to set email alerts
|

Precise Interference of RNA–Protein Interaction by CRISPR-Cas13-Mediated Peptide Competition

Meng Li,
Dan Li,
Leiruo Lin
et al.

Abstract: RNA–protein interactions are essential nodes of cellular regulatory circuits and play critical roles in normal physiology and disease. However, the precise roles of individual RNA–protein interactions remain elusive. Here we report a method for precise interference of endogenous RNA interacting with the RNA binding protein (RBP). TTP is an RBP that recognizes the AU-rich element (ARE) of mRNA via the binding domain TZF and represses gene expression. We engineer Cas13b, a class 2 type VI CRISPR-Cas endonuclease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While often called catalytically dead Cas13 (dCas13), the resulting HEPN-deficient Cas13 retains the pre-crRNA processing RNase activity and thus remains capable of multiplexing. dCas13 can be used as a programmable RNA-binding protein (RBP), allowing it to act as a competitive inhibitor of endogenous RBPs on a specific transcript [ 34 ]. Similarly, other functional RNA signals such as splice sites, polyadenylation signals and start codons of a specific transcript can be targeted by dCas13 to modulate splicing [ 11 ], polyadenylation [ 35 ] and translation initiation [ 36 ], respectively.…”
Section: Engineering Rna With Crispr-dcas13mentioning
confidence: 99%
“…While often called catalytically dead Cas13 (dCas13), the resulting HEPN-deficient Cas13 retains the pre-crRNA processing RNase activity and thus remains capable of multiplexing. dCas13 can be used as a programmable RNA-binding protein (RBP), allowing it to act as a competitive inhibitor of endogenous RBPs on a specific transcript [ 34 ]. Similarly, other functional RNA signals such as splice sites, polyadenylation signals and start codons of a specific transcript can be targeted by dCas13 to modulate splicing [ 11 ], polyadenylation [ 35 ] and translation initiation [ 36 ], respectively.…”
Section: Engineering Rna With Crispr-dcas13mentioning
confidence: 99%
“…Additionally, Li et al demonstrated a method to stabilize transcripts that have known negative regulator binding sites by directing dCas13 fused to the negative regulator's RNA-binding domain (TTP in their study), competing the native negative regulator off of the transcript of interest thereby increasing its abundance (Figure 2d). [66] While these are innovative strategies, the further development of direct protein-based methods for both translational repression and activation in eukaryotic cells will likely depend on the continued study and characterization of RBP function. RNA networks are often regulated by many RBPs in concert which can complicate the determination of their individual effects.…”
Section: Effectors For Repressing or Amplifying Translationmentioning
confidence: 99%
“…demonstrated a method to stabilize transcripts that have known negative regulator binding sites by directing dCas13 fused to the negative regulator's RNA‐binding domain (TTP in their study), competing the native negative regulator off of the transcript of interest thereby increasing its abundance (Figure 2d). [66] …”
Section: Effectors For Engineering Programmable Rbp With Diverse Func...mentioning
confidence: 99%